Mussel Inspired Chemistry and Bacteria Derived Polymers for Oral Mucosal Adhesion and Drug Delivery - Owji, Nazanin; Mandakhbayar, Nandin; Gregory, David A.; Marcello, Elena; Kim, Hae-won; Roy, Ipsita; Knowles, Jonathan C. (Frontiers in Bioengineering and Biotechnology, 2021)
Ulceration of the oral mucosa is common, can arise at any age and as a consequence of the pain lessens enjoyment and quality of life. Current treatment options often involve the use topical corticosteroids with poor drug delivery systems and inadequate contact time. In order to achieve local controlled delivery to the lesion with optimal adhesion, we utilized a simple polydopamine chemistry technique inspired by mussels to replicate their adhesive functionality. This was coupled with production of a group of naturally produced polymers, known as polyhydroxyalkanoates (PHA) as the delivery system. Initial work focused on the synthesis of PHA using Pseudomonas mendocina CH50; once synthesized and extracted from the bacteria, the PHAs were solvent processed into films. Polydopamine coating was subsequently achieved by immersing the solvent cast film in a polymerized dopamine solution. Fourier Transform Infrared Spectroscopy (FTIR) spectroscopy confirmed functionalization of the PHA films via the presence of amine groups. Further characterization of the samples was carried out via surface energy measurements and Scanning Electron Microscopy (SEM) micrographs for surface topography. An adhesion test via reverse compression testing directly assessed adhesive properties and revealed an increase in polydopamine coated samples. To further identify the effect of surface coating, LIVE/DEAD imaging and Alamar Blue metabolic activity evaluated attachment and proliferation of fibroblasts on the biofilm surfaces, with higher cell growth in favor of the coated samples. Finally, in vivo biocompatibility was investigated in a rat model where the polydopamine coated PHA showed less inflammatory response over time compared to uncoated samples with sign of neovascularization. In conclusion, this simple mussel inspired polydopamine chemistry introduces a step change in bio-surface functionalization and holds great promise for the treatment of oral conditions.